Changes in research on language barriers in health care since 2003: A cross-sectional review study. (February 2016) - Schwei, Rebecca J.; Del Pozo, Sam; Agger-Gupta, Niels; Alvarado-Little, Wilma; Bagchi, Ann; Chen, Alice Hm; Diamond, Lisa; Gany, Francesca; Wong, Doreena; Jacobs, Elizabeth A.
Abstract: Background: Understanding how to mitigate language barriers is becoming increasingly important for health care providers around the world. Language barriers adversely affect patients in their access to health services; comprehension and adherence; quality of care; and patient and provider satisfaction. In 2003, the United States (US) government made a major change in national policy guidance that significantly affected limited English proficient patients' ability to access language services. Objective: The objectives of this paper are to describe the state of the language barriers literature inside and outside the US since 2003 and to compare the research that was conducted before and after a national policy change occurred in the US. We hypothesize that language barrier research would increase inside and outside the US but that the increase in research would be larger inside the US in response to this national policy change. Methods: We reviewed the research literature on language barriers in health care and conducted a cross sectional analysis by tabulating frequencies for geographic location, language group, methodology, research focus and specialty and compared the literature before and after 2003. Results: Our sample included 136 studies prior to 2003 and 426 studies from 2003 to 2010. In the 2003–2010 time period there was a new interest in studying the providers' perspective instead of or in addition to the patients' perspective. The methods remained similar between periods with greater than 60% of studies being descriptive and 12% being interventions. Conclusions: There was an increase in research on language barriers inside and outside the US and we believe this was larger due to the change in the national policy. We suggest that researchers worldwide should move away from simply documenting the existence of language barriers and should begin to focus their research on documenting how language concordant care influences patient outcomes, providing evidence for interventions that mitigate language barriers, and evaluating the cost effectiveness of providing language concordant care to patients with language barriers. We think this is possible if funding agencies around the world begin to request proposals for these types of research studies. Together, we can begin document meaningful ways to provide high quality health care to patients with language barriers.